The effect of giomer’s preheating on fluoride release - Muthiary Nitzschia Nur Iswary Winanto; Irfan Dwiandhono; Setiadi Warata Logamarta; Rinawati Satrio; Aris Aji Kurniawan (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2022)
Background: Secondary caries occur due to imperfect plaque control. Prolong the protective and therapeutic effects can be done with restorative materials that release fluoride. Now composite resins have been developed a new restorative hybrid material with new matrix component, namely giomer. Giomer composition containing surface pre reacted glass ionomer (S-PRG) as a major source of fluoride production. Increasing the mechanical strength and minimize microleakage to prevent secondary caries can be done with preheating treatment. Purpose: This study is conducted to determine the effect of preheating temperature on the release of giomer’s fluoride. Methods: This study used 9 cylindrical samples in 10 mm diameter and 2 mm thickness each group, divided into 3 groups and 3 subgroups. Group 1: preheating at 37°C for 30 minutes. Group 2: preheating at 60°C for 30 minutes. Group 3: as a control group (without preheating treatment). Each group divided into 3 subgroups immersion, on day 1, day 7 and day 14 with artificial saliva. Fluoride release test was conducted by Spectrophotometer. IBM's SPSS Statistics used for the Data analysis. Results: The addition of preheating treatment decrease the amount of fluoride release. One-way ANOVA test showed a significant difference (P < 0.05). A significant difference between groups and sub groups showed in LSD test (P < 0.05). Conclusion: The group without preheating treatment has highest fluoride release and the 60°C preheating treatment group was the lowest. Addition of preheating treatment may increase the mechanical strength and minimize microleakage, but also descrease the amount of fluoride release.